Refocusing Spiritual Assessment in Enhancing Student Learning Motivation in Contemporary Islamic Education: A Systematic Literature Review - Abdullah Abdullah; M. Yusuf; Mundiro Lailatul Muawaroh; Moh. Ismail (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This article explores the potential application of spiritual assessment in contemporary Islamic education to enhance students' learning motivation. To achieve this objective, the article employs a Systematic Literature Review (SLR) method. The study was conducted systematically using the Watase Uake tool. The data for this study consisted of articles indexed in Q1, Q2, Q3, and Q4 journals. These articles were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique. Following identification, screening, and eligibility, 26 articles were included in the final analysis and examined using a meta-synthesis approach. The review findings indicate that spiritual assessment positively impacts learning motivation by helping students find meaning and purpose in their learning. Implementing spiritual assessment can help identify and strengthen students’ spiritual values, thereby enhancing their engagement and academic performance.